Olimpo do 5º ano: deusas gregas - Silva, Bruna de Lima; Braga, Ana Paula Mendes de Oliveira; Reis , Geissyane Aparecida Oliveira dos; Reis, Fabielle Ferreira da Silva dos; Bernhardt, Cristiane Otilia Colossi (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf